1992
DOI: 10.1111/j.1751-1097.1992.tb04258.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodestruction of Tumor Cells by Induction of Endogenous Accumulation of Protoporphyrin Ix: Enhancement by 1, 10‐phenanthroline

Abstract: Rapidly proliferating transformed mammalian cells can be photodestroyed in vitro upon inducing the accumulation of endogenous protoporphyrin IX (Proto). Proto biosynthesis and accumulation were triggered by manipulation of the porphyrin-heme biosynthetic pathway. Proto accumulation in cultured cells was induced by treatment with 1.0 mM delta-aminolevulinic acid (ALA), a naturally occurring 5-carbon amino acid, for 3.5 h. In darkness, significant Proto accumulation became evident within 3.5 h of incubation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Schick et al (1995) found that although stimulation of normal human keratinocytes with epidermal growth factor α (EGF-α), a cytokine stimulating the proliferation of epidermal and epithelial cells, resulted in higher cytotoxicities with ALA-PDT, activation of two skin squamous cell carcinoma lines did not have any effects. Rebeiz et al (1992) observed a significant increase in PpIX accumulation when resting splenocytes were activated with the mitogenic lectin concavalin A. A similar effect was reported by RittenhouseDiakun et al (1995) when human peripheral blood lymphocytes were stimulated with three different mitogens.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Schick et al (1995) found that although stimulation of normal human keratinocytes with epidermal growth factor α (EGF-α), a cytokine stimulating the proliferation of epidermal and epithelial cells, resulted in higher cytotoxicities with ALA-PDT, activation of two skin squamous cell carcinoma lines did not have any effects. Rebeiz et al (1992) observed a significant increase in PpIX accumulation when resting splenocytes were activated with the mitogenic lectin concavalin A. A similar effect was reported by RittenhouseDiakun et al (1995) when human peripheral blood lymphocytes were stimulated with three different mitogens.…”
Section: Discussionsupporting
confidence: 68%
“…Such studies have explored the role of ALA incubation time (Dietel et al, 1996;Krammer and Uberriegler, 1996;Gibson et al, 1997) and concentration (Krammer and Uberriegler, 1996;Gibson et al, 1997;Moan et al, 1998), cell type (Iinuma et al, 1994;Steinback et al, 1995;Wyld et al, 1997), cell cycle (Moan et al, 1998), proliferation status (Rebeiz et al, 1992;Schick et al, 1995;Momma et al, 1997), serum presence (Hanania and Malik, 1992;Fukuda et al, 1993), iron availability (Hanania and Malik, 1992;Iinuma et al, 1994;Rittenhouse-Diakun et al, 1995;Tan et al, 1997), pH (Bermudez Moretti et al, 1993;Krammer and Uberriegler, 1996;Bech et al, 1997;Wyld et al, 1998), glucose (Dietel et al, 1996), and temperature (Dietel et al, 1996). More detailed studies examined the effect of some of these factors on specific enzymes of the haem biosynthetic pathway (Schoenfeld et al, 1988;Gibson et al, 1998).…”
mentioning
confidence: 99%
“…Substances such as griseofulvin and hexachlorobenzene have already been used to induce porphyrin accumulation in hepatic cells in vitro (Visser et al, 1991). More recently, 1,10-phenanthroline has been shown to double the amount of ALA-induced protoporphyrin accumulation in rapidly proliferating cells (Rebeiz et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Poorlydifferentiated cells (KLE) showed fewer fluorescence corresponding to a longer doubling time. Rebeiz et al (5) showed that stimulated splenocytes with rapid turnover produced more Pp IX compared to resting splenocytes. Iinuma et al (12) evaluated different cell lines of varied origin (excluded endometrial cells) and compared the doubling time to PpIX cellular contents after ALA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Heme biosynthesis is essential to life and occurs in all aerobic cells.The administration of exogenous ALA induces accumulation of Pp IX (photosensitizer) which represents the fluorescenting substance (1). In general, malignant cells of epithelial origin accumulate more Pp IX than their normal counterparts (2,3,4,5,6). The capacity of neoplastic endometrial cells to accumulate ALA induced Pp IX has not been investigated until now.…”
mentioning
confidence: 99%